Al-Ta’āruf ‘alā al-Islām al-‘Aqlānī: Dirāsah ‘an al-Maqālāt al-Ṣadirah fī al-Wasā’il al-Maṭbū’ah fī al-Fatrah al-Mumtaddah min 1911-1942 - Imas Emalia (Center for Study of Islam and Society (PPIM) Syarif Hidayatullah State Islamic University, 2010)
This article describes the efforts of several Islamic organizations like the Sarekat Islam (1911), Muhammadiyah (1912), and Persjarikatan Oelama (1913) in transforming the Javanese paradigm, particularly of those who were cultured in quackery and mysticism. The analysis in this article relies on news and articles that were published in newspapers and Islamic journals from 1911 to1942. This article also aims to discuss various crucial problems in Javanese society in the twentieth century, ranging from the social, political, economic, and cultural sphere to religious life. Moreover, this article also portrays the development of the press and local mass media in Java and how they carried out their missionary movements by using rational standardsDOI: 10.15408/sdi.v17i1.469